Air cargo revenue management: a state-of-the-art review. (2nd May 2023) - Srinivasan, Dhandabani; Amit, R.K.; Chiang, Wen-Chyuan
In addition to serving high-value-to-weight goods, the air cargo market is expanding substantially mainly because of globalisation and the need for increased responsiveness in supply chains. At the same time, the theory of air cargo revenue management is far from the contemporary practices because of cargo-specific complexities like uncertain, multidimensional capacities, variable tendering, and forwarder's market power. This paper surveys the scientific contributions relevant to air cargo revenue management. We provide a comprehensive review of the developments in both quantity and pricing revenue management decisions. Additionally, we substantiate each decision with the appropriate dynamic programming formulation, which helps in highlighting the extensions to the current literature. We conclude our discussion by enumerating the potential prospects that are great revenue-yielding opportunities. This review links theoretical contributions and practical problems and serves as the signpost for the 30-year-old air cargo revenue management.